Feeding tube use in patients with head and neck cancer. Issue 12 (29th January 2014) - Lewis, Sherri L.; Brody, Rebecca; Touger–Decker, Riva; Parrott, James S.; Epstein, Joel
Abstract Background Use of a prophylactic feeding tube before concurrent chemotherapy and radiotherapy (CRT) for patients with head and neck cancer is often debated. Methods A retrospective, exploratory study of 109 veterans with stage III/IV head and neck cancer who completed standard CRT was conducted. Relationships among 3 feeding tube status groups: prophylactic feeding tube (PFT), reactive feeding tube (RFT), and no feeding tube (no‐FT) were compared for clinical outcomes. Results Patients with a PFT had significantly less weight loss during CRT, fewer nutrition‐related emergency department visits or hospitalizations, and higher proportions of chemotherapy cycles completed compared to those with an RFT or no‐FT. At 12 months post‐CRT, there was no relationship between the use of a PFT and 100% feeding tube dependency. Conclusion Use of a PFT in this veteran population with stage III/IV head and neck cancer produced better outcomes when compared to both an RFT or no feeding tube without higher rates of long‐term dysphagia. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1789–1795, 2014